Pengembangan Alat Evaluasi Pembelajaran Berbasis Android Melalui Aplikasi Quizziz pada Materi Puisi Siswa Kelas X SMA Nurul Amaliyah Tanjung Morawa - Rahma Yani (Medan Resource Center, 2021)
This research aimed to describe the development process, practicality, validity, and feasibility of using an android-based learning evaluation tool through the quizizz application on